Dean's award and student excellence ceremony / Syahida Fathiah Ahmad Kamal and Assoc. Prof. Dr. Mahmathi Karuppannan - Ahmad Kamal, Syahida Fathiah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On May 24, 2023, the Academic Office, Faculty of Pharmacy organised the Dean's Awards and Student Excellence Ceremony at Lecture Hall 7, FF4 Building. The ceremony aimed to celebrate students who received the Dean's Awards during February 2023 examinations and also recognise students for their excellent achievement in co-curricular activities. A total of 16 students from the Bachelor of Pharmacy (PH240) program received the Dean's Awards, and one student from the Master in Pharmacy Practice (PH772) program received the Faculty Postgraduate Award.